Perancangan Aplikasi Terenkripsi Dengan Menerapkan Metode Secret Sharing Asmuth Bloom - Evi Amelia Tarigan (STMIK Budi Darma, 2018)
Conventional cryptographic algorithms cannot be applied to solve a plaintext (message) into several ciphertext pieces because conventional cryptographic algorithms can only produce a ciphertext from a plaintext (message) In this case, cryptography can be applied, namely Asmuth-Bloom's secret sharing. The methodology used to analyze and design the Asmuth-Bloom secret sharing cryptographic application software is the Waterfall methodology. This research is intended to produce a learning software that is able to display work processes from Asmuth-Bloom's secret sharing and applications from Asmuth-Bloom's secret sharing. The working procedure described by the software includes the process of forming keys, the process of forming shadows and the process of combining shadow.